WANITA DALAM PANDANGAN AGAMA DAN BANGSA - Ulya Kencana (An Nisa'a, 2012)
Woman representing the part of type of human being which up to now in various cleft of world tend to assumed as second class compared to a men. Background of that condition is sometimes supported also by interpretation of opinion and cultures of group socialize, so this condition is continuing without a lot of changing. This article want to study how view of religion and nation about woman from contemporary and historical dimension. Even do not exhaustively; this study is strived able to express fact and reality about domiciling woman from some point of view of religion and nation.